2016
DOI: 10.1016/j.geomorph.2015.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Planform and mobility in the Meaípe-Maimbá embayed beach on the South East coast of Brazil

Abstract: Please cite this article as: Albino, Jacqueline, Jiménez, José A., Oliveira, Tiago C.A., Planform and mobility in the meaípe-maimbá embayed beach on the South East coast of Brazil, Geomorphology (2015),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
4
0
4
Order By: Relevance
“…Tabela 1 -Parâmetros estatísticos de comparação dos dados de ondas medidos e modelados. Modificado de Albino et al (2016b).…”
Section: Métodos Banco De Dados Gowunclassified
“…Tabela 1 -Parâmetros estatísticos de comparação dos dados de ondas medidos e modelados. Modificado de Albino et al (2016b).…”
Section: Métodos Banco De Dados Gowunclassified
“…Ajustes, seja empregando a espiral logarítmica (YASSO, 1965; CARVALHO; CLAUDINO-SALES, 2017), a parabólica (HSU et al 1987), ou a tangente hiperbólica (MORENO; KRAUS, 1999), apesar de conhecidos, eram pouco aplicados no país. No entanto, foi a partir da disponibilização do programa MEPBAY do ajuste parabólico de Hsu (HSU et al 1987), de uso simples (VARGAS et al 2002), que o método teve aplicação mais ampla (KLEIN et al 2003;SILVEIRA et al 2010;ALBINO et al 2016;BARRETO et al 2016, entre outros).…”
Section: Praiasunclassified
“…Small crystalline islands, concentrated near the beach's center, modify the wave incidence patterns along the beach. The NE-SW coastline is exposed to intense E and SE winds, related to trade winds and frontal systems, respectively (Albino et al, 2016b). Examining waves from the WaveWatch III model, Pianca et al (2010) reported that mean wave peak direction is predominantly from the east over the entire year except during fall when southern waves prevail.…”
Section: Study Areamentioning
confidence: 99%
“…Bluff erosion is already considered a devastating process, with England, for example, estimating a cost of one million pounds per year spent on maintenance and improvement of coastal defenses (Lee, 2005). Along the Espírito Santo coast, particularly the narrow Maimbá beach backed by sea bluffs, current bluff retreat has required government investment to try to stop the erosion process after the destruction of an important coastal road (Albino et al, 2001;Machado et al, 2003;Albino et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation